Budget impact of eribulin in metastatic breast cancer in Russian Federation - S. K. Zyryanov; D. Yu. Belousov (Izdatelstvo OKI, 2018)
Breast cancer is one of the most wide spread oncological disease and metastatic breast cancer is very severe, because of its high resistance. One of the recent drugs aimed for this group of patients is еribulin, which is microtubules dynamics inhibitor, leading to non-functional tubuline complex formation. Statistically relevant and clinically signifi cant еribulin action according to total survival was approved among HER2-negative and triple negative breast cancer. Eribulin is the only cytostatic approved as a monotherapy that leads to relevant and significant life prolongation among metastatic breast cancer patients, who had several regimens of therapy before.Aim. To determine budget impact and life years saved aft er adding Halaven® (еribulin) to the offi cial lists for metastatic breast cancer treatment.Methodology. Th is PHe was conducted according to standart implemented in the RF. All the breast cancer patients according to the state statics were included. The modelling horizon was 5 years. Drugs comparison are docetaxel, paclitaxel, kapezitabine, gemzitabine, vinorelbine, eribulin. Randomized controlled clinical trials investigating safety and effi cacy of these drugs, as well as performing head-to-head comparisons of some of them, were used as data source on safety and efficacy. A «decision tree» model was then constructed in order to estimate healthcare costs and patients outcomes. Two parameters were chosen as criteria for eff ectiveness assessment - overall survival and survival without progression. The results were used to perform Budget Impact Analysis (BIA) and evaluation of phramacoeconomic expediency and health impact.Results. Eribulin instead of standart therapy prolongs the patients' life for 76 days. Budget impact analysis was performed to the terms of the treatment and adverse events correction. The profit of the eribulin treatment for every patient was 462858 rubles for 5 years or 5.59% of the budget impact. Sensitivity analysis confirms result stability, however, when price increase reaches 25%, the profit is 321356 rubles or 3.85% of the budget impact.Conclusion. It has been determined that eribulin is the most clinically and economically effective drug for metastatic breast cancer after 2nd line chemotherapy with the lowest budgetary burden.